A high temperature wear resistant dry brake friction plate material and preparation method thereof
By adding Mo and Y2O3 to the iron-copper alloy matrix for strengthening, and combining the use of high-entropy alloy and composite lubricating phase, the wear problem of the iron-copper alloy friction sheet under high temperature conditions is solved, and the comprehensive effect of low friction coefficient, low wear rate and high mechanical properties is achieved.
Patent Information
- Application Number
- CN202410707451.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-03
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-06-03
AI Technical Summary
The existing iron-copper alloy friction sheets have abrasive wear and peeling wear effects under high temperature conditions, resulting in fluctuations in friction coefficient and increased wear rate, and the mechanical strength and reliability of the material are affected.
By adding Mo and Y2O3 to the iron-copper alloy matrix to achieve solid solution strengthening and dispersion strengthening, combining high-entropy alloy reinforced phase (Al-Cr-Fe-Ni-Ti) and composite lubricated phase (CaF2+BaF2+Ag), their ratio is regulated to reduce adhesion wear and abrasive wear, forming a stable lubricating film.
The comprehensive performance of low friction coefficient and low wear rate under high temperature conditions is achieved, which improves the hardness, strength and service life of the material, while reducing material costs.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to a high temperature wear resistant dry brake friction plate material and a preparation method thereof, belonging to the technical field of alloy friction materials. Background Art
[0002] Dry brake friction pads have strict requirements on the heat resistance and wear resistance of friction pad materials at high temperatures because of the lack of oil on the surface, rapid temperature rise and severe wear. Iron-copper alloys are widely used in high-speed rail brake pads and heavy-duty vehicle dry brake friction pads due to their high strength, hardness and wear resistance. However, the existing iron-copper alloy friction pads have strong abrasive wear and delamination wear effects under high temperature conditions, causing a large number of furrows and peeling on the friction surface, resulting in fluctuations in the friction coefficient and increased wear rate. Therefore, in order to achieve higher reliability and service life of the friction pad, its thickness and weight are usually large, which reduces the energy and space utilization of the vehicle. Therefore, how to improve the tribological properties of iron-copper alloys under high temperature conditions of dry braking is a problem worthy of attention.
[0003] Chinese patent CN104384503A prepared an iron-copper-based powder metallurgy anti-friction material, and its samples need to be immersed in oil. When used for a long time on dry brake friction pads, the performance fluctuates greatly and the maintenance requirements are high. Chinese patent CN106086585A reduces the friction coefficient and wear rate by adding graphite and Al2O3 to the iron-copper alloy matrix, but if excellent friction performance is to be maintained under extreme braking and high temperature conditions, the high content of graphite and Al2O3 will have an adverse effect on the mechanical strength and reliability of the material. Chinese patents CN112011748B and CN110284083B improve the heat resistance and service life of the material by adding carbon fiber to the copper alloy, but as the carbon fiber content increases, the initiation and expansion of cracks inside the material intensify, which will have an adverse effect on its mechanical properties. Chinese patent CN102703161A improves the self-lubricating properties of the material by adding an appropriate amount of Ti3SiC2 to the copper matrix, but its matrix is pure copper with low strength and hardness, making it difficult to use in heavy load and strong impact conditions. Chinese patent CN1594622A strengthens the matrix by adding rare earth elements, but since no strengthening phase and lubricating phase are added, the friction performance of the material under high temperature conditions is slightly improved. The above research results show that the strengthening effect of traditional strengthening phases on the iron-copper alloy matrix is limited, and when the content is high, it will have an adverse effect on the uniformity of the material's organization and mechanical strength; at the same time, the modification effect of a single strengthening phase or lubricating phase is limited. Therefore, it is necessary to study new lubricating phase and strengthening phase composite formulas and material preparation methods to further improve the friction and wear performance of iron-copper alloys at high temperatures.
[0004] Studies have shown that adding alloying elements to iron-copper alloys can improve hardness and strength, but there is no report on compounding Mo and Y2O3 to improve the wear resistance of iron-copper alloys. At the same time, high entropy alloys (Al-Cr-Fe-Ni-Ti) have face-centered cubic and body-centered cubic structures. Face-centered cubic structure powders have good plasticity, and body-centered cubic structure powders have high strength, so they can effectively improve the mechanical strength and wear resistance of materials. Some researchers have conducted research on high entropy alloys (Al-Cr-Fe-Ni-Ti), but there is no research on regulating their ratio and addition amount to improve the wear resistance of iron-copper alloys. In addition, CaF2 and BaF2 have high chemical stability and thermal stability. They will form a lubricating film on the friction surface at high temperature, keeping the friction coefficient low and stable. Ag can reduce the damage of hard wear debris to the friction surface, thereby weakening the three-body wear mechanism. Existing technologies have achieved the use of Ag and CaF2-BaF2, but there is no research on adding the composite lubricating phase (CaF2+BaF2+Ag) and high entropy alloy (Al-Cr-Fe-Ni-Ti) into the iron-copper alloy and precisely regulating their mutual coupling properties. Summary of the invention
[0005] In order to overcome the defects of the prior art, one of the purposes of the present invention is to provide a high-temperature wear-resistant dry brake friction plate material; the material strengthens the iron-copper alloy matrix by precisely controlling the addition amounts of Mo and Y2O3; a high-entropy alloy strengthening phase (Al-Cr-Fe-Ni-Ti) is added to the iron-copper alloy to improve the wear resistance; a composite lubricating phase (CaF2+BaF2+Ag) is used, and its ratio is adjusted so that the CaF2-BaF2 weakening two-body wear effect and the Ag weakening three-body wear effect are superimposed on each other, providing a method of simultaneously adding a high-entropy alloy strengthening phase (Al-Cr-Fe-Ni-Ti) and a composite lubricating phase (CaF2+BaF2+Ag), and by adjusting their ratios, the (CaF2+BaF2+Ag) weakening adhesive wear effect and the (CaF2+BaF2+Ag) weakening abrasive wear effect are coupled to reduce the friction coefficient and wear rate.
[0006] A second object of the present invention is to provide a method for preparing a high temperature wear resistant dry brake friction plate material.
[0007] To achieve the purpose of the present invention, the following technical solutions are provided.
[0008] A high temperature wear resistant dry brake friction plate material, taking the total mass of the raw material of the friction plate material as 100%, wherein the components and their mass fractions are as follows:
[0009] Iron-copper alloy matrix 69.0%~89.0%,
[0010] High entropy alloy strengthening phase 5.0%~15.0%,
[0011] Composite lubricating phase 6.0%~16.0%.
[0012] The raw material of the iron-copper alloy matrix is a mixed powder composed of copper (Cu), aluminum (Al), nickel (Ni), iron (Fe), molybdenum (Mo) and yttrium trioxide (Y2O3). Taking the total mass of the raw material of the friction plate material as 100%, the components and mass fractions of the raw material of the iron-copper alloy matrix are as follows:
[0013] Copper (Cu) 16.0% ~ 32.0%, aluminum (Al) 2.0% ~ 7.0%, nickel (Ni) 10.0% ~ 19.0%, iron (Fe) 26.0% ~ 45.0%, molybdenum (Mo) 0.5% ~ 1.0%, yttrium trioxide (Y2O3) 0.5% ~ 1.0%.
[0014] The high entropy alloy strengthening phase (Al-Cr-Fe-Ni-Ti) is a mixed powder composed of aluminum (Al), chromium (Cr), iron (Fe), nickel (Ni) and titanium (Ti). Taking the total mass of the raw materials of the high entropy alloy strengthening phase as 100%, the components and their mass fractions are: aluminum (Al) 6.0% to 7.0%, chromium (Cr) 14.0% to 18.0%, iron (Fe) 15.0% to 18.0%, nickel (Ni) 55.0% to 60.0%, and titanium (Ti) 4.0% to 5.0%.
[0015] The high entropy alloy strengthening phase is a mixed powder obtained by mixing powdery raw materials Al, Cr, Fe, Ni and Ti by wet ball milling.
[0016] Preferably, the high entropy alloy strengthening phase is prepared according to the following method:
[0017] Al powder, Cr powder, Fe powder, Ni powder and Ti powder are wet ball-milled under inert gas protection, n-heptane is added as a process control agent, the ball-to-material ratio is 8:1-10:1, the rotation speed is 300 r / min-350 r / min, the ball milling time is 150 h-200 h, the ball milling is stopped every 5 min-10 min, and the ball milling is continued after stopping for 2 min-3 min to prepare a mixed powder as a high entropy alloy strengthening phase; wherein the amount of n-heptane added is 1% of the total mass of the raw materials of the high entropy alloy strengthening phase.
[0018] The composite lubricating phase (CaF2+BaF2+Ag) is a mixed powder composed of calcium fluoride (CaF2), barium fluoride (BaF2) and silver (Ag). Taking the total mass of the raw materials of the composite lubricating phase as 100%, the components and their mass fractions are: CaF2 30.0%~35.0%, BaF2 30.0%~35.0%, Ag 30.0%~40.0%.
[0019] The composite lubricating phase is a mixed powder obtained by mixing powdery raw materials CaF2, BaF2 and Ag by wet ball milling.
[0020] Preferably, the composite lubricating phase is prepared as follows:
[0021] CaF2 powder, BaF2 powder and Ag powder are wet-milled under inert gas protection, n-heptane is added as a process control agent, the ball-to-material ratio is 3:1-4:1, the rotation speed is 300r / min-350r / min, the ball milling time is 8h-10h, and the ball milling is stopped every 5min-10min. After stopping for 2min-3min, the ball milling is continued to prepare a mixed powder as a composite lubricating phase; wherein the amount of n-heptane added is 1% of the total mass of the raw materials of the composite lubricating phase.
[0022] A method for preparing a high temperature wear resistant dry brake friction plate material according to the present invention comprises: mixing raw materials of an iron-copper alloy matrix, a high entropy alloy strengthening phase and a composite lubricating phase by mechanical ball milling to obtain a mixed powder, and then hot pressing and sintering the mixed powder to prepare the material.
[0023] Specifically, the mechanical ball milling mixing steps are as follows:
[0024] The raw materials of the iron-copper alloy matrix, the high entropy alloy strengthening phase and the composite lubricating phase are dry-milled under the protection of inert gas, with a ball-to-material ratio of 1:1-2:1, a rotation speed of 100 r / min-150 r / min, a ball milling time of 8 h-10 h, and the ball milling is stopped every 5 min-10 min, and the ball milling is continued after stopping for 2 min-3 min; a mixed powder is prepared; the grinding jar and the grinding balls used in the ball milling are made of tungsten carbide cemented carbide.
[0025] Specifically, the hot pressing sintering steps are as follows:
[0026] The mixed powder prepared by ball milling was placed into a mold and placed in a spark plasma sintering furnace for hot pressing and sintering with a vacuum degree of less than 1×10 -1Pa, the heating rate is 100℃ / min~150℃ / min, the sintering temperature is 850℃~900℃, the applied pressure is 35MPa~40MPa, the constant temperature and pressure are maintained for 5min~10min to end the hot pressing sintering, and the material is cooled to room temperature with the furnace to prepare a high temperature wear resistant dry brake friction plate material.
[0027] The mold used in hot pressing sintering is usually a graphite mold.
[0028] In the present invention, the ball-to-material ratio refers to the ratio of the weight of the grinding body (grinding balls) in the ball mill to the weight of the material.
[0029] Beneficial Effects
[0030] (1) The present invention provides a high temperature wear resistant dry brake friction plate material, wherein the friction plate material generates a solid solution strengthening effect by adding Mo element to the iron-copper alloy matrix and generates a dispersion strengthening effect by adding Y2O3 to be dispersed in the iron-copper alloy matrix. Compared with the existing iron-copper alloy matrix strengthening technology, the present invention combines the solid solution strengthening effect of Mo element with the dispersion strengthening effect of Y2O3 by accurately controlling the relative content of Mo and Y2O3, so that the friction plate material required by the present invention has excellent structural uniformity, hardness and strength.
[0031] (2) The present invention provides a high temperature wear resistant dry brake friction plate material, wherein the friction plate material adds a high entropy alloy strengthening phase (Al-Cr-Fe-Ni-Ti) to an iron-copper alloy matrix, thereby reducing the plowing and peeling effects of the contact surface by means of a pinning mechanism without affecting the strength of the matrix, thereby improving the wear resistance and service life of the matrix under high temperature dry friction conditions. The amount of high entropy alloy strengthening phase added will have a significant impact on the comprehensive performance of the friction plate material. If there are too many high entropy alloy strengthening phases, the friction plate material will have a decrease in mechanical properties due to decreased interface wettability and excessive impurities; if there are too few high entropy alloy strengthening phases, it is difficult to effectively improve the wear resistance of the friction plate material. Compared with iron-copper alloys with commonly used strengthening phases such as Al2O3, the present invention improves the bonding force between the strengthening phase and the iron-copper alloy matrix by accurately controlling the ratio and content of the high entropy alloy strengthening phase, thereby achieving a balance between mechanical properties and friction properties.
[0032] (3) The present invention provides a high temperature wear resistant dry brake friction plate material, wherein the friction plate material forms a stable lubricating film with low shear strength on the friction surface by adding a composite lubricating phase (CaF2+BaF2+Ag) to an iron-copper alloy matrix, so as to improve the lubrication performance of the matrix under extreme braking high temperature conditions. The content of CaF2, BaF2, and Ag will have a significant impact on the performance of the friction plate material. If there is too much CaF2-BaF2 and too little Ag, the friction plate material will have a decrease in strength and wear resistance due to a decrease in internal bonding force and excessive grain boundary impurities; if there is too little CaF2-BaF2 and too much Ag, it is difficult to effectively improve the lubrication performance of the friction plate material under high temperature conditions. Compared with iron-copper alloys with commonly used lubricating phases such as graphite added, the present invention improves the bonding force between the lubricating phase and the iron-copper alloy matrix by accurately controlling the content of CaF2-BaF2 and Ag, thereby achieving an improvement in the lubrication performance of the friction plate material under high temperature and room temperature conditions.
[0033] (4) The present invention provides a high temperature wear resistant dry brake friction plate material, wherein the friction plate material improves the anti-friction and anti-wear properties of the material by simultaneously adding a high entropy alloy strengthening phase (Al-Cr-Fe-Ni-Ti) and a composite lubricating phase (CaF2+BaF2+Ag) to an iron-copper alloy matrix. Compared with a material containing only one added phase, the present invention achieves the coupling of lubrication and anti-friction properties under high temperature conditions by accurately regulating the content of the high entropy alloy strengthening phase and the composite lubricating phase, so that the friction plate material has both high strength and low friction coefficient and wear rate.
[0034] (5) The present invention provides a high-temperature wear-resistant dry brake friction pad material, the friction pad material has a hardness of 202HV~213HV, a compressive strength of 885MPa~1002MPa, and a bending strength of 724MPa~919MPa, and has high hardness and strength; the friction pad material has a low and stable friction coefficient and wear rate under high-temperature friction conditions, and exhibits good comprehensive performance; at the same time, the material has low cost, high economic benefits, and a wide range of applications, and is suitable for dry friction working components such as high-speed rail brake pads and heavy-duty vehicle dry brake friction pads, and has a relatively broad application prospect.
[0035] (6) The present invention provides a method for preparing a high temperature wear resistant dry brake friction plate material, wherein the iron-copper alloy raw material powder, high entropy alloy strengthening phase powder and composite lubricating phase powder are ball milled under inert gas protection, the obtained mixed powder is placed in a sintering furnace for hot pressing and sintering, and the mixed powder is cooled in the furnace after sintering. Compared with the existing preparation technology, the preparation process of the present invention is obtained through multiple experiments, which can improve the uniformity and strength of the material on the one hand, and improve the density and hardness on the other hand. DETAILED DESCRIPTION
[0036] The present invention is described in detail below in conjunction with specific embodiments, but is not intended to limit the present invention.
[0037] A high temperature wear resistant dry brake friction plate material, taking the total mass of the raw material of the friction plate material as 100%, wherein the components and their mass fractions are as follows:
[0038] Iron-copper alloy matrix 69.0%~89.0%,
[0039] High entropy alloy strengthening phase 5.0%~15.0%, Composite lubricating phase 6.0%~16.0%.
[0040] The raw material of the iron-copper alloy matrix is a mixed powder composed of copper (Cu), aluminum (Al), nickel (Ni), iron (Fe), molybdenum (Mo) and yttrium trioxide (Y2O3). Taking the total mass of the raw material of the friction plate material as 100%, the components and mass fractions of the raw material of the iron-copper alloy matrix are as follows:
[0041] Copper (Cu) 16.0% ~ 32.0%, aluminum (Al) 2.0% ~ 7.0%, nickel (Ni) 10.0% ~ 19.0%, iron (Fe) 26.0% ~ 45.0%, molybdenum (Mo) 0.5% ~ 1.0%, yttrium trioxide (Y2O3) 0.5% ~ 1.0%.
[0042] The high entropy alloy strengthening phase (Al-Cr-Fe-Ni-Ti) is a mixed powder composed of aluminum (Al), chromium (Cr), iron (Fe), nickel (Ni) and titanium (Ti). Taking the total mass of the raw materials of the high entropy alloy strengthening phase as 100%, the components and their mass fractions are: aluminum (Al) 6.0% to 7.0%, chromium (Cr) 14.0% to 18.0%, iron (Fe) 15.0% to 18.0%, nickel (Ni) 55.0% to 60.0%, and titanium (Ti) 4.0% to 5.0%.
[0043] The high entropy alloy strengthening phase is a mixed powder obtained by mixing powdery raw materials Al, Cr, Fe, Ni and Ti by wet ball milling.
[0044] Preferably, the high entropy alloy strengthening phase is prepared according to the following method:
[0045] Al powder, Cr powder, Fe powder, Ni powder and Ti powder are wet ball-milled under inert gas protection, n-heptane is added as a process control agent, the ball-to-material ratio is 8:1-10:1, the rotation speed is 300 r / min-350 r / min, the ball milling time is 150 h-200 h, the ball milling is stopped every 5 min-10 min, and the ball milling is continued after stopping for 2 min-3 min to prepare a mixed powder, which is a high entropy alloy strengthening phase; wherein the amount of n-heptane added is 1% of the total mass of the raw materials of the high entropy alloy strengthening phase.
[0046] The composite lubricating phase (CaF2+BaF2+Ag) is a mixed powder composed of calcium fluoride (CaF2), barium fluoride (BaF2) and silver (Ag). Taking the total mass of the raw materials of the composite lubricating phase as 100%, the components and their mass fractions are: CaF2 30.0%~35.0%, BaF2 30.0%~35.0%, Ag 30.0%~40.0%.
[0047] The composite lubricating phase is a mixed powder obtained by mixing powdery raw materials CaF2, BaF2 and Ag by wet ball milling.
[0048] Preferably, the composite lubricating phase is prepared as follows:
[0049] CaF2 powder, BaF2 powder and Ag powder are wet ball-milled under inert gas protection, n-heptane is added as a process control agent, the ball-to-material ratio is 3:1-4:1, the rotation speed is 300r / min-350r / min, the ball milling time is 8h-10h, and the ball milling is stopped every 5min-10min. After stopping for 2min-3min, the ball milling is continued to prepare a mixed powder as a composite lubricating phase.
[0050] The amount of n-heptane added is 1% of the total mass of the raw materials of the composite lubricating phase.
[0051] A method for preparing a high temperature wear resistant dry brake friction plate material according to the present invention comprises: mixing raw materials of an iron-copper alloy matrix, a high entropy alloy strengthening phase and a composite lubricating phase by mechanical ball milling to obtain a mixed powder, and then hot pressing and sintering the mixed powder to prepare the material.
[0052] Specifically, the mechanical ball milling mixing steps are as follows:
[0053] The raw materials of the iron-copper alloy matrix, the high entropy alloy strengthening phase and the composite lubricating phase are dry-milled under the protection of inert gas, with a ball-to-material ratio of 1:1-2:1, a rotation speed of 100 r / min-150 r / min, a ball milling time of 8 h-10 h, and the ball milling is stopped every 5 min-10 min, and the ball milling is continued after stopping for 2 min-3 min; a mixed powder is prepared; the grinding jar and the grinding balls used in the ball milling are made of tungsten carbide cemented carbide.
[0054] Specifically, the hot pressing sintering steps are as follows:
[0055] The mixed powder prepared by ball milling was placed into a mold and placed in a spark plasma sintering furnace for hot pressing and sintering with a vacuum degree of less than 1×10 -1 Pa, the heating rate is 100℃ / min~150℃ / min, the sintering temperature is 850℃~900℃, the applied pressure is 35MPa~40MPa, the constant temperature and pressure are maintained for 5min~10min to end the hot pressing sintering, and the material is cooled to room temperature with the furnace to prepare a high temperature wear resistant dry brake friction plate material.
[0056] The mold used in hot pressing sintering is usually a graphite mold.
[0057] The ball-to-material ratio refers to the ratio of the weight of the grinding body (grinding balls) in the ball mill to the weight of the material.
[0058] Example 1
[0059] A method for preparing a high temperature wear resistant dry brake friction plate material, the preparation method comprising:
[0060] A mixed powder consisting of 16.0 g of Cu, 7.0 g of Al, 19.0 g of Ni, 45.0 g of Fe, 1.0 g of Mo and 1.0 g of Y2O3 was weighed as the raw material of the iron-copper alloy matrix, and the raw material of the iron-copper alloy matrix, 5.0 g of the high entropy alloy strengthening phase (Al-Cr-Fe-Ni-Ti) and 6.0 g of the composite lubricating phase (CaF2+BaF2+Ag) were mixed by dry ball milling under argon protection, with a ball-to-material ratio of 1:1, a rotation speed of 100 r / min, a ball milling time of 8 h, and the ball milling was stopped every 5 min and continued after stopping for 2 min; a mixed powder was prepared; the grinding jar and grinding balls used in the ball milling were made of tungsten carbide cemented carbide.
[0061] The mixed powder was loaded into a graphite mold and placed in a spark plasma sintering furnace for hot pressing and sintering with a vacuum degree of less than 1×10 -1 Pa, the heating rate is 100℃ / min, the sintering temperature is 850℃, the applied pressure is 35MPa, the constant temperature and pressure are maintained for 5min, the hot pressing sintering is terminated, and the furnace is cooled to room temperature to prepare a high temperature wear-resistant dry brake friction pad material.
[0062] The high entropy alloy strengthening phase (Al-Cr-Fe-Ni-Ti) is a mixed powder obtained by wet ball milling of powdered raw materials Al, Cr, Fe, Ni and Ti, and is specifically prepared by the following method:
[0063] Weigh 6.0 g of Al powder, 14.0 g of Cr powder, 15.0 g of Fe powder, 60.0 g of Ni powder and 5.0 g of Ti powder, and perform wet ball milling under argon protection. Add 1 g of n-heptane as a process control agent, the ball-to-material ratio is 8:1, the rotation speed is 300 r / min, the ball milling time is 150 h, stop every 10 min, and continue ball milling after stopping for 2 min to prepare a mixed powder, which is the strengthening phase of the high entropy alloy.
[0064] The composite lubricating phase (CaF2+BaF2+Ag) is a mixed powder obtained by mixing powdered raw materials of calcium fluoride (CaF2), barium fluoride (BaF2) and silver (Ag) by wet ball milling, and is specifically prepared by the following method:
[0065] Weigh 30.0g of CaF2 powder, 30.0g of BaF2 powder, and 40.0g of Ag powder, and perform wet ball milling under argon atmosphere protection, add 1g of n-heptane as a process control agent, the ball-to-material ratio is 3:1, the rotation speed is 300r / min, the ball milling time is 8h, stop every 10min, and continue ball milling after stopping for 2min to prepare a mixed powder, which is a composite lubricating phase.
[0066] The performance test of a high temperature wear resistant dry brake friction plate material prepared in this embodiment is as follows:
[0067] (1) The hardness of the steel is 213 HV when tested by Vickers hardness tester.
[0068] (2) The mechanical properties were tested using a CMT-5205 universal material testing machine, with the compression and three-point bending displacement rates being 0.1 mm / min. The test results showed that the compressive strength of the friction plate material was 1002 MPa, and the bending strength was 919 MPa.
[0069] (3) The high-temperature tribological properties were evaluated using a HT-1000 high-temperature friction and wear tester. The dual ball was a 316 stainless steel ball, the load was 10 N, the sliding speed was 0.1 m / s, the friction radius was 5 mm, the running time was 30 min, and the test temperatures were 25 °C and 700 °C, respectively. The test showed that the average friction coefficient of the friction plate material at room temperature was 0.29, and the average wear rate was 1.2 × 10 -4 mm 3 / N·m; the average friction coefficient at 700℃ is 0.50, and the average wear rate is 4.8×10 -4 mm 3 / N·m, with good anti-friction and anti-wear properties.
[0070] The above test results indicate that a high temperature wear resistant dry brake friction plate material is prepared in this embodiment. The friction plate material has a low and stable friction coefficient and wear rate under high temperature conditions and has good friction reduction and anti-wear properties.
[0071] Example 2
[0072] A method for preparing a high temperature wear resistant dry brake friction plate material, the preparation method comprising:
[0073] A mixed powder consisting of 32.0 g of Cu, 2.0 g of Al, 10.0 g of Ni, 34.0 g of Fe, 0.5 g of Mo and 0.5 g of Y2O3 was weighed as a raw material for an iron-copper alloy matrix, and the raw material of the iron-copper alloy matrix, 10.0 g of a high-entropy alloy strengthening phase and 11.0 g of a composite lubricating phase were mixed by dry ball milling under argon protection, with a ball-to-material ratio of 1.5:1, a rotation speed of 120 r / min, a ball milling time of 9 h, and the ball milling was stopped every 7 min and continued after stopping for 2 min; a mixed powder was prepared; the grinding jar and grinding balls used in the ball milling were made of tungsten carbide cemented carbide.
[0074] The mixed powder was loaded into a graphite mold and placed in a spark plasma sintering furnace for hot pressing and sintering with a vacuum degree of less than 1×10 -1 Pa, the heating rate is 120℃ / min, the sintering temperature is 880℃, the applied pressure is 38MPa, the constant temperature and pressure are maintained for 7min, the hot pressing sintering is terminated, and the furnace is cooled to room temperature to prepare a high temperature wear resistant dry brake friction pad material.
[0075] The high entropy alloy strengthening phase (Al-Cr-Fe-Ni-Ti) is a mixed powder obtained by wet ball milling of powdered raw materials Al, Cr, Fe, Ni and Ti, and is specifically prepared by the following method:
[0076] Weigh 7.0 g of Al powder, 18.0 g of Cr powder, 16.0 g of Fe powder, 55.0 g of Ni powder and 4.0 g of Ti powder, and perform wet ball milling under argon protection. Add 1 g of n-heptane as a process control agent, the ball-to-material ratio is 9:1, the rotation speed is 320 r / min, the ball milling time is 180 h, stop every 8 min, and continue ball milling after stopping for 2 min to prepare a mixed powder, which is the strengthening phase of the high entropy alloy.
[0077] The composite lubricating phase (CaF2+BaF2+Ag) is a mixed powder obtained by mixing powdered raw materials of calcium fluoride (CaF2), barium fluoride (BaF2) and silver (Ag) by wet ball milling, and is specifically prepared by the following method:
[0078] Weigh 32.0g of CaF2 powder, 33.0g of BaF2 powder, and 35.0g of Ag powder, and perform wet ball milling under argon atmosphere protection, add 1g of n-heptane as a process control agent, the ball-to-material ratio is 3.5:1, the rotation speed is 330r / min, the ball milling time is 9h, stop every 8min, and continue ball milling after stopping for 2min to prepare a mixed powder, which is a composite lubricating phase.
[0079] The performance test of a high temperature wear resistant dry brake friction plate material prepared in this embodiment is as follows:
[0080] (1) The hardness of the steel is 202 HV when tested by Vickers hardness tester.
[0081] (2) The mechanical properties were tested using a CMT-5205 universal material testing machine, with the compression and three-point bending displacement rates being 0.1 mm / min. The test results showed that the compressive strength of the friction plate material was 956 MPa, and the bending strength was 823 MPa.
[0082] (3) The high-temperature tribological properties were evaluated using a HT-1000 high-temperature friction and wear tester. The dual ball was a 316 stainless steel ball, the load was 10 N, the sliding speed was 0.2 m / s, the friction radius was 5 mm, the running time was 30 min, and the test temperatures were 25 °C and 700 °C, respectively. The test showed that the average friction coefficient of the friction plate material at room temperature was 0.24, and the average wear rate was 1.0 × 10 -4 mm 3 / N·m; the average friction coefficient at 700℃ is 0.43, and the average wear rate is 4.3×10 -4 mm 3 / N·m, with good anti-friction and anti-wear properties.
[0083] The above test results indicate that a high temperature wear resistant dry brake friction plate material is prepared in this embodiment. The friction plate material has a low and stable friction coefficient and wear rate under high temperature conditions and has good friction reduction and anti-wear properties.
[0084] Example 3
[0085] A method for preparing a high temperature wear resistant dry brake friction plate material, the preparation method comprising:
[0086] A mixed powder consisting of 20.0 g of Cu, 4.0 g of Al, 12.0 g of Ni, 32.0 g of Fe, 0.5 g of Mo and 0.5 g of Y2O3 was weighed as a raw material for an iron-copper alloy matrix, and the raw material of the iron-copper alloy matrix, 15.0 g of a high-entropy alloy strengthening phase and 16.0 g of a composite lubricating phase were mixed by dry ball milling under argon protection, with a ball-to-material ratio of 2:1, a rotation speed of 150 r / min, a ball milling time of 10 h, and the ball milling was stopped every 10 min and continued after stopping for 3 min; a mixed powder was prepared; the grinding jar and grinding balls used in the ball milling were made of tungsten carbide cemented carbide.
[0087] The mixed powder was loaded into a graphite mold and placed in a spark plasma sintering furnace for hot pressing and sintering with a vacuum degree of less than 1×10 -1 Pa, the heating rate is 150℃ / min, the sintering temperature is 900℃, the applied pressure is 40MPa, the constant temperature and pressure are maintained for 10min, the hot pressing sintering is terminated, and the furnace is cooled to room temperature to prepare a high temperature wear-resistant dry brake friction pad material.
[0088] The high entropy alloy strengthening phase (Al-Cr-Fe-Ni-Ti) is a mixed powder obtained by wet ball milling of powdered raw materials Al, Cr, Fe, Ni and Ti, and is specifically prepared by the following method:
[0089] Weigh 6.0 g of Al powder, 16.0 g of Cr powder, 18.0 g of Fe powder, 55.0 g of Ni powder and 5.0 g of Ti powder, and perform wet ball milling under argon protection. Add 1 g of n-heptane as a process control agent, the ball-to-material ratio is 10:1, the rotation speed is 350 r / min, the ball milling time is 200 h, stop every 5 min, and continue ball milling after stopping for 3 min to prepare a mixed powder, which is the strengthening phase of the high entropy alloy.
[0090] The composite lubricating phase (CaF2+BaF2+Ag) is a mixed powder obtained by mixing powdered raw materials of calcium fluoride (CaF2), barium fluoride (BaF2) and silver (Ag) by wet ball milling, and is specifically prepared by the following method:
[0091] Weigh 35.0g of CaF2 powder, 35.0g of BaF2 powder, and 30.0g of Ag powder, and perform wet ball milling under argon atmosphere protection, add 1g of n-heptane as a process control agent, the ball-to-material ratio is 4:1, the rotation speed is 350r / min, the ball milling time is 10h, stop every 5min, and continue ball milling after stopping for 3min to prepare a mixed powder, which is a composite lubricating phase.
[0092] The performance test of a high temperature wear resistant dry brake friction plate material prepared in this embodiment is as follows:
[0093] (1) The hardness of the steel is 208 HV when tested by Vickers hardness tester.
[0094] (2) The mechanical properties were tested using a CMT-5205 universal material testing machine, with the compression and three-point bending displacement rates being 0.1 mm / min. The test results showed that the compressive strength of the friction plate material was 885 MPa, and the bending strength was 724 MPa.
[0095] (3) The high-temperature tribological properties were evaluated using a HT-1000 high-temperature friction and wear tester. The dual ball was a 316 stainless steel ball, the load was 10 N, the sliding speed was 0.2 m / s, the friction radius was 5 mm, the running time was 30 min, and the test temperatures were 25 °C and 700 °C, respectively. The test showed that the average friction coefficient of the friction plate material at room temperature was 0.21, and the average wear rate was 0.7×10 -4 mm 3 / N·m; the average friction coefficient at 700℃ is 0.39, and the average wear rate is 3.9×10 -4 mm 3 / N·m, with good anti-friction and anti-wear properties.
[0096] The above test results indicate that a high temperature wear resistant dry brake friction plate material is prepared in this embodiment. The friction plate material has a low and stable friction coefficient and wear rate under high temperature conditions and has good friction reduction and anti-wear properties.
[0097] Comparative Example 1
[0098] Relative to Example 1, Comparative Example 1 provides a friction plate material, the raw materials of which are an iron-copper alloy matrix: 16.0 g of Cu, 7.0 g of Al, 19.0 g of Ni, 45.0 g of Fe, wherein Mo and Y2O3 are not added; other conditions are consistent with those of Example 1.
[0099] The performance of the friction plate material of comparative example 1 is compared with that of the friction plate material of embodiment 1. The results are shown in Table 1. The hardness, compressive strength and bending strength of the friction plate material of comparative example 1 decrease, and the wear rate increases. This is because when Mo and Y2O3 are missing, the refinement and dispersion strengthening effects cannot be produced, the hardness and strength of the material decrease, resulting in reduced wear resistance.
[0100] Table 1 Comparison of Comparative Example 1 with Example 1
[0101]
[0102] Comparative Example 2
[0103] Compared with Example 3, Comparative Example 2 provides a friction plate material, in which the composite lubricating phase (CaF2+BaF2+Ag) in Example 3 is replaced by graphite as the lubricating phase; other conditions are consistent with Example 3.
[0104] The performance of the friction plate material of Comparative Example 2 was compared with that of the friction plate material of Example 3. The results are shown in Table 2. At 700°C, the friction coefficient and wear rate of the friction plate material of Comparative Example 2 increased. This is because the composite lubricating phase (CaF2+BaF2+Ag) has excellent lubrication performance under high temperature environment, while the lubrication ability of graphite is relatively poor under high temperature environment, resulting in an increase in the friction coefficient and aggravated wear of the friction plate material prepared in Comparative Example 2.
[0105] Table 2 Comparison of Comparative Example 2 with Example 3
[0106]
[0107] Comparative Example 3
[0108] Relative to Example 3, Comparative Example 3 provides a friction plate material, in which the composite strengthening phase (Al-Cr-Fe-Ni-Ti) in Example 3 is replaced by Al2O3 as the strengthening phase; other conditions are consistent with Example 3.
[0109] The performance of the friction plate material of comparative example 3 is compared with that of the friction plate material of embodiment 3. The results are shown in Table 3. The compressive strength and bending strength of the friction plate material of comparative example 3 are reduced, and the wear rate is increased. This is because the interface bonding force between Al2O3 and the iron-copper alloy is lower than the interface bonding force between the composite strengthening phase (Al-Cr-Fe-Ni-Ti) and the iron-copper alloy, resulting in a decrease in material strength, and the material is more likely to peel off from the surface during the friction process, so the wear resistance is reduced.
[0110] Table 3 Comparison of Comparative Example 3 with Example 3
[0111]
[0112] Comparative Example 4
[0113] Relative to Example 2, Comparative Example 4 provides a friction plate material, with a specific composition ratio of: 34.0g Cu, 9.0g Al, 10.0g Ni, 24.0g Fe, 2.0g Mo, 2.0g Y2O3, 17.0g high entropy alloy strengthening phase (Al-Cr-Fe-Ni-Ti), and 2.0g composite lubricating phase (CaF2+BaF2+Ag); other conditions are consistent with Example 2.
[0114] The performance of the friction plate material of comparative example 4 is compared with that of the friction plate material of embodiment 2. The results are shown in Table 4. The hardness, compressive strength and flexural strength of the friction plate material of comparative example 4 decrease, and the friction coefficient and wear rate increase. The main reasons are as follows: the Fe content in the iron-copper alloy matrix decreases, and the content of other alloy elements and strengthening phases increases, resulting in changes in the phase composition of the alloy, an increase in impurity elements, and a decrease in the bonding force of the internal phase interface of the material, so the hardness, compressive strength and flexural strength decrease, and the wear rate increases; at the same time, the content of the high entropy alloy strengthening phase (Al-Cr-Fe-Ni-Ti) is too much, and the content of the composite lubricating phase (CaF2+BaF2+Ag) is too little, which makes it difficult for the material to form a stable lubricating film on the surface during friction and wear, so the friction coefficient and wear rate increase.
[0115] Table 4 Comparison of Comparative Example 4 with Example 2
[0116]
[0117] Comparative Example 5
[0118] Relative to Example 3, Comparative Example 5 provides a friction plate material, in which the composite lubricating phase (CaF2+BaF2+Ag) in Example 3 is replaced by 8g of CaF2 and 8g of BaF2 as the composite lubricating phase; when preparing the composite lubricating phase, 50.0g of CaF2 powder and 50.0g of BaF2 powder are weighed and wet ball milled under the protection of argon atmosphere; other conditions are consistent with Example 3.
[0119] The performance of the friction plate material of Comparative Example 5 is compared with that of the friction plate material of Example 3. The results are shown in Table 5. The compressive strength and bending strength of the friction plate material of Comparative Example 5 are reduced. This is because the interface bonding force between the composite lubricating phase (CaF2+BaF2) and the iron-copper alloy is lower than the interface bonding force between Ag and the iron-copper alloy. When the content of the composite lubricating phase (CaF2+BaF2) is too much, cracks are likely to initiate and expand at the grain boundaries of the material, resulting in a decrease in strength.
[0120] Table 5 Comparison of Comparative Example 5 with Example 3
[0121]
[0122] Comparative Example 6
[0123] Compared with Example 3, Comparative Example 6 provides a friction plate material, in which the composite lubricating phase (CaF2+BaF2+Ag) in Example 3 is replaced by pure Ag; other conditions are consistent with Example 3.
[0124] The performance of the friction plate material of Comparative Example 6 is compared with that of the friction plate material of Example 3. The results are shown in Table 6. At 700°C, the friction coefficient and wear rate of the friction plate material of Comparative Example 6 increase. This is because the lubricating effect of Ag is weaker than that of CaF2+BaF2 under high temperature environment. When the material does not contain CaF2+BaF2, the lubricating ability at high temperature decreases, resulting in an increase in friction coefficient and aggravated wear.
[0125] Table 6 Comparison of Comparative Example 6 with Example 3
[0126]
[0127] Comparative Example 7
[0128] Relative to Example 2, Comparative Example 7 provides a friction plate material, wherein the specific composition ratio of the high entropy alloy strengthening phase (Al-Cr-Fe-Ni-Ti) is: 3.0 g of Al powder, 20.0 g of Cr powder, 11.0 g of Fe powder, 62.0 g of Ni powder and 4.0 g of Ti powder; other conditions are consistent with Example 2.
[0129] The performance of the friction plate material of Comparative Example 7 is compared with that of the friction plate material of Example 2. The results are shown in Table 7. The compressive strength and bending strength of the friction plate material of Comparative Example 7 are reduced. This is because the reduction of Al and Fe elements in the high entropy alloy strengthening phase causes the interface bonding force between the high entropy alloy strengthening phase and the iron-copper alloy matrix to decrease, and cracks are prone to initiation and expansion at the grain boundaries of the material, which leads to a decrease in strength.
[0130] Table 7 Comparative Example 7 compared with Example 2
[0131]
[0132] Comparative Example 8
[0133] Relative to Example 3, Comparative Example 8 provides a friction plate material, in which high-energy ball milling is not performed when preparing the composite lubricating phase (CaF2+BaF2+Ag), and the ball milling process is as follows: dry ball milling under argon protective atmosphere, with a ball-to-material ratio of 1:1, a rotation speed of 100 r / min, a ball milling time of 8 h, stopping every 15 min, and continuing the ball milling after stopping for 2 min to prepare a mixed powder, which is a composite lubricating phase; other conditions are consistent with Example 3.
[0134] The performance of the friction plate material of Comparative Example 8 was compared with that of the friction plate material of Example 3. The results are shown in Table 8. The strength of the friction plate material of Comparative Example 8 decreased. This is because high-energy ball milling was not performed when preparing the composite lubricating phase (CaF2+BaF2+Ag) in Comparative Example 8, resulting in low dispersion and surface chemical energy of the composite lubricating phase (CaF2+BaF2+Ag) powder, and decreased bonding strength with the iron-copper alloy matrix.
[0135] Table 8 Comparative Example 8 compared with Example 3
[0136]
[0137] Comparative Example 9
[0138] Relative to Example 3, Comparative Example 9 provides a friction plate material, in which high-energy ball milling is not performed when preparing the reinforcing phase (Al-Cr-Fe-Ni-Ti), and the ball milling process is as follows: dry ball milling under argon protective atmosphere, with a ball-to-material ratio of 1:1, a rotation speed of 100 r / min, a ball milling time of 8 h, stopping every 15 min, and continuing the ball milling after stopping for 2 min to prepare a mixed powder as the reinforcing phase; other conditions are consistent with Example 3.
[0139] The performance of the friction plate material of Comparative Example 9 was compared with that of the friction plate material of Example 3. The results are shown in Table 9. The strength of the friction plate material of Comparative Example 9 decreased and the wear rate increased. This is because the strengthening phase (Al-Cr-Fe-Ni-Ti) of Comparative Example 9 was not subjected to high-energy ball milling, the raw material powder was not completely formed into a high-entropy alloy powder, and the powder dispersion and surface chemical energy were low, and the bonding force with the iron-copper alloy matrix was reduced, resulting in a decrease in the strengthening effect on the iron-copper alloy.
[0140] Table 9 Comparative Example 9 compared with Example 3
[0141]
[0142] Comparative Example 10
[0143] Compared with Example 1, Comparative Example 10 provides a friction plate material. During the preparation process, the hot pressing sintering process parameters are: the vacuum degree is less than 1×10 -1 Pa, the heating rate is 100°C / min, the sintering temperature is 920°C, the applied pressure is 30MPa, the constant temperature and pressure are maintained for 5min, the hot pressing sintering is terminated, and the furnace is cooled to room temperature; other conditions are consistent with Example 1.
[0144] The performance of the friction plate material of Comparative Example 10 was compared with that of the friction plate material of Example 1. The results are shown in Table 10. The hardness and strength of the friction plate material of Comparative Example 10 decreased, and the wear rate increased. This is because the sintering temperature was too high during the preparation of Comparative Example 10, resulting in component segregation of the iron-copper alloy matrix, and the sintering pressure was too low, resulting in a decrease in the hardness and strength of the material.
[0145] Table 10 Comparative Example 10 compared with Example 1
[0146]
Claims
1. A high temperature wear resistant dry brake friction plate material, characterized by: Taking the total mass of the raw materials of the friction plate material as 100%, the components and their mass fractions are as follows: Iron-copper alloy matrix 69.0%~89.0%, High entropy alloy strengthening phase 5.0%~15.0%, Composite lubricating phase 6.0% to 16.0%; Taking the total mass of the raw materials of the friction plate material as 100%, the components and mass fractions of the raw materials of the iron-copper alloy matrix are as follows: Copper 16.0% to 32.0%, aluminum 2.0% to 7.0%, nickel 10.0% to 19.0%, iron 26.0% to 45.0%, molybdenum 0.5% to 1.0%, yttrium trioxide 0.5% to 1.0%; The high entropy alloy strengthening phase is a mixed powder formed by mixing powdered raw materials Al, Cr, Fe, Ni and Ti by wet ball milling; taking the total mass of the raw materials of the high entropy alloy strengthening phase as 100%, the components and their mass fractions are: aluminum 6.0% to 7.0%, chromium 14.0% to 18.0%, iron 15.0% to 18.0%, nickel 55.0% to 60.0%, titanium 4.0% to 5.0%; The composite lubricating phase is a mixed powder obtained by wet ball milling of powdered raw materials CaF2, BaF2 and Ag; taking the total mass of the raw materials of the composite lubricating phase as 100%, the components and their mass fractions are: CaF2 30.0%-35.0%, BaF2 30.0%-35.0%, Ag 30.0%-40.0%.
2. The high temperature wear resistant dry brake friction pad material according to claim 1, characterized in that: The high entropy alloy strengthening phase is prepared according to the following method: Al powder, Cr powder, Fe powder, Ni powder and Ti powder are wet ball-milled under inert gas protection, n-heptane is added, the ball-to-material ratio is 8:1-10:1, the rotation speed is 300r / min-350r / min, the ball milling time is 150h-200h, and the ball milling is stopped every 5min-10min. After stopping for 2min-3min, the ball milling is continued to prepare a mixed powder, which is a high entropy alloy strengthening phase.
3. The high temperature wear resistant dry brake friction pad material according to claim 2, characterized in that: The amount of n-heptane added is 1% of the total mass of the high entropy alloy strengthening phase raw material.
4. A high temperature wear resistant dry brake friction pad material according to any one of claims 1 to 3, characterized in that: The composite lubricating phase is prepared according to the following method: CaF2 powder, BaF2 powder and Ag powder are wet ball-milled under inert gas protection, n-heptane is added as a process control agent, the ball-to-material ratio is 3:1-4:1, the rotation speed is 300r / min-350r / min, the ball milling time is 8h-10h, and the ball milling is stopped every 5min-10min. After stopping for 2min-3min, the ball milling is continued to prepare a mixed powder as a composite lubricating phase.
5. The high temperature wear resistant dry brake friction pad material according to claim 4, characterized in that: The amount of n-heptane added is 1% of the total mass of the raw materials of the composite lubricating phase.
6. A method for preparing a high temperature wear resistant dry brake friction pad material according to any one of claims 1 to 5, characterized in that: The raw materials of the iron-copper alloy matrix, the high entropy alloy strengthening phase and the composite lubricating phase are mixed by mechanical ball milling to obtain a mixed powder, and then the mixed powder is hot-pressed and sintered to prepare the product.
7. The method for preparing a high temperature wear resistant dry brake friction plate material according to claim 6, characterized in that: The steps of mechanical ball milling are as follows: The raw materials of the iron-copper alloy matrix, the high entropy alloy strengthening phase and the composite lubricating phase are dry-milled under the protection of inert gas, with a ball-to-material ratio of 1:1-2:1, a rotation speed of 100 r / min-150 r / min, a ball milling time of 8 h-10 h, and the ball milling is stopped every 5 min-10 min, and the ball milling is continued after stopping for 2 min-3 min; a mixed powder is prepared; the grinding jar and the grinding balls used in the ball milling are made of tungsten carbide cemented carbide.
8. The method for preparing a high temperature wear resistant dry brake friction plate material according to claim 6, characterized in that: The steps of hot pressing sintering are as follows: The mixed powder prepared by ball milling was placed into a mold and placed in a spark plasma sintering furnace for hot pressing and sintering with a vacuum degree of less than 1×10 -1 Pa, the heating rate is 100℃ / min~150℃ / min, the sintering temperature is 850℃~900℃, the applied pressure is 35MPa~40MPa, the constant temperature and pressure are maintained for 5min~10min to end the hot pressing sintering, and the material is cooled to room temperature with the furnace to prepare a high temperature wear resistant dry brake friction plate material.
Citation Information
Patent Citations
Self-lubricating copper-Ti3SiC2-NbSe2 composite material and preparation method thereof
CN102703161A
Ferrum- and copper-based powder metallurgy antifriction material and preparation method thereof
CN104384503A
Copper-iron base brake composite material and preparation method thereof
CN106086585A
A friction material, a brake pad including the friction material, and a method for preparing the brake pad.
CN110284083B
Copper-based powder metallurgy friction materials and their preparation methods
CN112011748B